2009
DOI: 10.1001/jama.2009.405
|View full text |Cite
|
Sign up to set email alerts
|

Bed Bugs (<emph type="ital">Cimex lectularius</emph>) and Clinical Consequences of Their Bites

Abstract: IMEX LECTULARIUS HAS BEEN known as a human parasite for thousands of years, but scientific studies of this insect are recent and limited. 1,2 International travel, immigration, changes in pest control practices, and insecticide resistance may have contributed to a recent resurgence of this blood-sucking insect in developed countries. 1,3 Bed bug infestations have been reported increasingly in homes, apartments, hotel rooms, hospitals, and dormitories in the United States since 1980 (TABLE 1). 1,21,22 For examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
365
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(370 citation statements)
references
References 64 publications
4
365
0
1
Order By: Relevance
“…7 Although bedbugs have not been implicated as vectors for disease transmission, they can cause dermatologic symptoms and be harmful to psychological health. 4,[8][9][10][11] Bedbugs can affect all socioeconomic groups and result in adverse economic consequences, including extermination costs, and damaged furniture. 3,5,12,13 The ecology and life cycle of bedbugs (most commonly CIMEX lectularius) make eradication difficult.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although bedbugs have not been implicated as vectors for disease transmission, they can cause dermatologic symptoms and be harmful to psychological health. 4,[8][9][10][11] Bedbugs can affect all socioeconomic groups and result in adverse economic consequences, including extermination costs, and damaged furniture. 3,5,12,13 The ecology and life cycle of bedbugs (most commonly CIMEX lectularius) make eradication difficult.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bed bug bites are known to cause various forms of cutaneous reactions, including minor itching, severe inflammation, and secondary infections. 5 In addition, bed bugs can be a cause of mental distress and overall physical discomfort. 2 Their cryptic nature and increasing resistance to a large variety of insecticides makes them difficult to detect and even more difficult to eliminate.…”
Section: Introductionmentioning
confidence: 99%
“…Hill and MacDonald found that bed bugs carry many pathogens including bacteria, viruses, protozoa, and parasitic worms [2]. Some scientists suggested that the risk is still present and more studies needed to be done on the other diseases that bed bugs can transmit to human [1,2,7].…”
Section: Health Effect On Humanmentioning
confidence: 99%
“…The reason for this resurgence is the less use of pesticides; however, some scientists mentioned that international immigration from developing to developed countries might be one of the reasons. Goddard and deShazo stated that this resurgence is due to the fact that bed bugs have developed a resistance to insecticides [2].…”
mentioning
confidence: 99%